Artistics: Colonial Cultural Costumes In Film Bumi Dan Manusia - Mochamad Ridwan Rosidin; Salsa Solli Nafsika; Hery Supiarza (Cinematology: Journal Anthology of Film and Television Studies, 2021)
The film Bumi Manusia directed by Hanung Bramantyo is an adaptation of a novel written by Paramoedya Ananta Toer with the same title. The story raised tells of the struggle of the indigenous people against various forms of colonialism. To describe the setting of the place and time of the film Bumi Manusia, represent it through costumes as a feature that the story occurred during the Dutch colonial period and the culture of colonialism occurred in the country. Costumes are a very vital marker during the Dutchcolonial period that can distinguish the social stratification between aristocrats and indigenous peoples. This study used a descriptive qualitative approach and data sources were obtained from the film Bumi Manusia. The data taken in this study were the costumes that distinguished the two parties between the colonizers or aristocrats and the indigenous people. The results of this study indicate that there are caste differences that are depicted through costumes during the colonialism era. Keywords — Artistics, Costumes, Colonial Culture, Bumi Manusia Film